The Effect of Soil Type on Touch Voltage and Step Voltage in the Grid Grounding System - Fitriani, Ayu; Panjaitan, Joel; Syahputra, Syofyan Anwar (Faculty of Engineering, Universitas Tanjungpura, 2024)
The grounding system is one of the security systems in substations to channel excess voltage caused by lightning strikes that occur at substations, as well as electrical equipment. To design a grounding system, there are several factors that must be considered, including the type of soil, the configuration of the grounding system, the resistivity of the soil, and the condition of the surrounding environment. The aim of this research is to determine the safe limits in the substation grid grounding system which is influenced by the type of soil and influences the touch voltage and step voltage, which can be dangerous to humans. The method used is simulation with the Finite Element Method (FEM) in the ETAP application. Finite Element Method (FEM) is a method that uses image mediation by assuming that the grounding system is an equipotential structure. The test results were deliberately carried out with larger substation area parameters and different soil types, so that the differences between the influence and appearance of touch voltage and step voltage can be seen clearly.